Revised dietary exposure assessment of the food enzyme triacylglycerol lipase from the genetically modified Aspergillus oryzae strain NZYM‐AL - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme triacylglycerol lipase (triacylglycerol acylhydrolase, EC 3.1.1.3) is produced with the genetically modified Aspergillus oryzae strain NZYM‐AL by Novozymes A/S. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that, under the intended conditions of use, this food enzyme did not give rise to safety concerns. Due to the implementation of a new methodology to estimate the dietary exposure to food enzymes in 2016, the European Commission requested EFSA to revise the exposure assessment of this food enzyme by using this new methodology. In this assessment, EFSA realigned the intended uses of this food enzyme to four food manufacturing processes. The dietary exposure was calculated to be up to 0.089 mg TOS/kg body weight (bw) per day in European populations. When combined with the no observed adverse effect level previously reported (49.1 mg TOS/kg bw per day, the lowest dose tested), the Panel derived a margin of exposure of at least 552. Based on the revised exposure estimate, the margin of exposure calculated thereof and the previous evaluation, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.